2021
DOI: 10.14740/gr1368
|View full text |Cite
|
Sign up to set email alerts
|

Primary Basidiobolomycosis of the Cecum in Immunocompetent Patients: Two Case Reports

Abstract: Colonic basidiobolomycosis is a rare fungal infection caused by Basidiobolus ranarum. Primary cecal basidiobolomycosis is an exceptionally rare condition. The study describes two cases of primary basidiobolomycosis of the cecum in immunocompetent male and female patients (one each). The patients presented with fever, abdominal pain, weight loss, eosinophilia, and high erythrocyte sedimentation rates. Computed tomography revealed wall thickening and mass lesions involving the cecum, suggesting malignancy. Right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In patients who do not respond to, or cannot tolerate, amphotericin B, Both drugs can also be used as second-line therapy [18] . if there is a clinical suspicion of GIB, empirical therapy with antifungal agents should be prescribed [1] . An additional medical treatment modality is Oral saturated solution of potassium iodide (SSKI), particularly before the availability of azoles; which is now replaced by itraconazole but it may still be prescribed in developing countries due to low cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who do not respond to, or cannot tolerate, amphotericin B, Both drugs can also be used as second-line therapy [18] . if there is a clinical suspicion of GIB, empirical therapy with antifungal agents should be prescribed [1] . An additional medical treatment modality is Oral saturated solution of potassium iodide (SSKI), particularly before the availability of azoles; which is now replaced by itraconazole but it may still be prescribed in developing countries due to low cost.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 100,000 fungi worldwide, but only about 150 of them are pathogenic [1] . Basidiobolus ranarum is a filamentous fungus in the Entomophthorales group of the Zygomycota family that has been associated with emergent fungal infection characterized by chronic subcutaneous induration [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…A review suggested that the pathogenesis of basidiobolomycosis is due to the production of lipases and proteases by the fungus. 1 , 2 Some possible risk factors include ranitidine, a known risk factor for bacterial gastroenteritis, which decreases acidity in the stomach, promoting the survival of the organisms. Another possible risk factor is chronic smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The infection often presents with non-specific clinical and radiological features; therefore, it should be considered in the differential diagnosis in endemic regions. 1 We report a rare case of basidiobolomycosis in a 16-year-old male with liver and gastrointestinal involvement.…”
Section: Introductionmentioning
confidence: 93%
“…Basidiobolus ranarum is the etiologic agent of subcutaneous chronic zygomycosis in man. Cases of invasive zygomycotic infection caused by B. ranarum in young humans and their clinical and pathological features have been reviewed with highlight reported from different countries (Hussein et al, 2021;Nazir et al, 1997). This suggests that gene or genome duplication may be an important feature of B. ranarum evolution and suggests that B. ranarum may have mechanisms which favors their difference from other related taxa or possessing unique properties (Elya and De Fine Licht, 2021;Henk and Fisher, 2012).…”
Section: Basidiobolusmentioning
confidence: 99%